Contrasting impact of corticosteroids on anti-PD-1 immunotherapy efficacy for tumor histologies located within or outside the central nervous system. (2nd December 2018) - Maxwell, Russell; Luksik, Andrew S.; Garzon-Muvdi, Tomas; Hung, Alice L.; Kim, Eileen S.; Wu, Adela; Xia, Yuanxuan; Belcaid, Zineb; Gorelick, Noah; Choi, John; Theodros, Debebe; Jackson, Christopher M.; et al.
ABSTRACT: Immune checkpoint blockade targeting programmed cell death protein 1 (PD-1) is emerging as an important treatment strategy in a growing list of cancers, yet its clinical benefits are limited to a subset of patients. Further investigation of tumor-intrinsic predictors of response and how extrinsic factors, such as iatrogenic immunosuppression caused by conventional therapies, impact the efficacy of anti-PD-1 therapy are paramount. Given the widespread use of corticosteroids in cancer management and their immunosuppressive nature, this study sought to determine how corticosteroids influence anti-PD-1 responses and whether their effects were dependent on tumor location within the periphery versus central nervous system (CNS), which may have a more limiting immune environment. In well-established anti-PD-1-responsive murine tumor models, corticosteroid therapy resulted in systemic immune effects, including severe and persistent reductions in peripheral CD4+ and CD8 + T cells. Corticosteroid treatment was found to diminish the efficacy of anti-PD-1 therapy in mice bearing peripheral tumors with responses correlating with peripheral CD8/Treg ratio changes. In contrast, in mice bearing intracranial tumors, corticosteroids did not abrogate the benefits conferred by anti-PD-1 therapy. Despite systemic immune changes, anti-PD-1-mediated antitumor immune responses remained intact during corticosteroid treatment in mice bearing intracranial tumors. These findings suggest that anti-PD-1 responses may be differentially impacted by concomitant corticosteroid use depending on tumor location within or outside the CNS. As an immune-specialized site, the CNS may potentially play a protective role against the immunosuppressive effects of corticosteroids, thus sustaining antitumor immune responses mediated by PD-1 blockade.